2011
DOI: 10.1103/physrevb.83.184411
|View full text |Cite
|
Sign up to set email alerts
|

Griffiths-like phase and magnetic correlations at high fields in Gd5Ge4

Abstract: Magnetic correlations appearing in polycrystalline Gd 5 Ge 4 are studied. On the one hand, ac susceptibility measurements as functions of temperature at several dc fields and frequencies show the existence of ferromagnetic (FM) and antiferromagnetic (AFM) correlations in the paramagnetic (PM) region, where a Griffiths-like phase appears below ∼225 K. The value for the effective magnetic moment within the Griffiths-like phase is 10.1 μ B . FM correlations also extended all the way into the AFM phase below ∼127 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 33 publications
5
22
0
1
Order By: Relevance
“…The softening of the down turn ∼ T * with increasing H indicates nonanalytic behavior of magnetization and thus further supports the existence of short‐range FMC. The resemblance of our experimental observations with other reports confirm the existence of the FMC. The observed T FMC in the present case is found to coincide with the T C of La 0.6 Sr 0.4 MnO 3 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The softening of the down turn ∼ T * with increasing H indicates nonanalytic behavior of magnetization and thus further supports the existence of short‐range FMC. The resemblance of our experimental observations with other reports confirm the existence of the FMC. The observed T FMC in the present case is found to coincide with the T C of La 0.6 Sr 0.4 MnO 3 .…”
Section: Resultssupporting
confidence: 92%
“…Now, we will discuss its robustness in comparison with other such reports in manganites and other magnetic oxides. It is imperative to mention here that in the earlier reports, such FMC were totally masked by the application of only few hundred/thousand Oe of H , making χ −1 ( T ) almost straight like CW behavior, i.e., the PM susceptibility overwhelms that of the FMC. Surprisingly, in our case even after 70 kOe the χ − 1 ( T ) in the FMC region is nonlinear, i.e., the FMC remains unmasked.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…These short-range FM correlations are characterized by unusually slow relaxation dynamics above the magnetic ordering temperature, which is observed in time-dependent magnetic relaxation measurements and are also manifested in the frequency dependence of ac susceptibility. 100 kOe (Pérez et al, 2011). Casanova et al (2005c) reported the presence of short-range competing FM and AFM correlations in Gd 5 Si x Ge 4Àx Ge-rich alloys for x ¼ 0, 0.2, and 0.4 in high magnetic fields ($140-150 kOe) at temperatures slightly below T N but greater than $80 K. In this area of H-T diagram, the magnetic-fieldinduced AFM-FM transition proceeds through an intermediate state, which the authors mark as a short-range correlation (SRC) region.…”
Section: Figure 28mentioning
confidence: 99%
“…Ouyang (2010) argues that the low-field region of the Gd 5 Si x Ge 4Àx x-T diagram should include the area of the Griffiths-like phase between the long-range magnetically ordered state and the truly paramagnetic region; the T G for x < 2 can be derived from the linear extrapolation of T C 's of the alloys with x > 2. Pérez et al (2011) also examined the low-field short-range magnetic correlations (Griffiths-like phase) in Gd 5 Ge 4 using ac magnetic susceptibility measurements. By using pulse magnetic fields as high as 400 kOe, Wu et al (2011) studied the same region (85 K < T < 105 K) of the Gd 5 Ge 4 H-T diagram and concluded that the intermediate state is paramagnetic.…”
Section: Figure 28mentioning
confidence: 99%